Measuring Corporate Governance Using Analytic Hierarchy Process (AHP): Case of Algerian Companies - HADJ-SAHRAOUI, Hamoudi; Chiboub, Rima (Journal of Finance & Corporate Governance, 2019)
During the last decades, and according to its effect on financial performance, the measuring of corporate governance systems has been the subject of many empirical studies. In this side and in order to arrange the Algerian companies, the Analytic Hierarchy Process (AHP), which is concerning as a multi-criteria decision-making method, has been used to analyze the data of 16 companies during the period 2010-2013. The findings are as follows: (1) in contrast to the property type which determines the financial performance, the relationships between corporate governance mechanisms and financial performance are weak and sometimes negative (2) according to AHP results, the corporate governance systems of private companies are the best.